2003
DOI: 10.1210/me.2003-0021
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the P2X7Nucleotide Receptor Reveals Its Regulatory Roles in Bone Formation and Resorption

Abstract: The P2X7 nucleotide receptor is an ATP-gated ion channel expressed widely in cells of hematopoietic origin. Our purpose was to explore the involvement of the P2X7 receptor in bone development and remodeling by characterizing the phenotype of mice genetically modified to disrupt the P2X7 receptor [knockout (KO)]. Femoral length did not differ between KO and wild-type (WT) littermates at 2 or 9 months of age, indicating that the P2X7 receptor does not regulate longitudinal bone growth. However, KO mice displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
262
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(282 citation statements)
references
References 23 publications
18
262
2
Order By: Relevance
“…This study also demonstrated large variations in the relative expression of the P2 receptors in osteoblasts, with mRNA for the P2X4 receptor being the most abundant [167]. Expression of the P2X7 receptor was first demonstrated in a subpopulation of human differentiated osteoblasts [169]; later studies also demonstrated expression in rat [158,167] and mouse osteoblasts [137]. Interestingly, a recent study claimed that P2X7 receptors are localised in caveolae in the plasma membranes of osteoblasts [170].…”
Section: Bonementioning
confidence: 88%
See 3 more Smart Citations
“…This study also demonstrated large variations in the relative expression of the P2 receptors in osteoblasts, with mRNA for the P2X4 receptor being the most abundant [167]. Expression of the P2X7 receptor was first demonstrated in a subpopulation of human differentiated osteoblasts [169]; later studies also demonstrated expression in rat [158,167] and mouse osteoblasts [137]. Interestingly, a recent study claimed that P2X7 receptors are localised in caveolae in the plasma membranes of osteoblasts [170].…”
Section: Bonementioning
confidence: 88%
“…The initial study by Ke et al [137] reported a decreased bone mineral content and periosteal circumference accompanied by decreased bone formation parameters and increased bone resorption parameters [137]. A separate study by Gartland et al [136] reported no differences in bone mineral density of trabecular bone, but an increase in cortical bone was observed.…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice in which P2X7 receptor function is disrupted (knockout) exhibit diminished periosteal bone formation and increased trabecular bone resorption [10] and impaired anabolic responses of the skeleton to mechanical load [11]. In cells of the osteoblast lineage, stimulation of the P2X7 receptor promotes differentiation and matrix mineralization [12].…”
Section: Introductionmentioning
confidence: 99%